Progression of Nigrostriatal Denervation in Cerebellar Multiple System Atrophy: A Prospective Study. (8th February 2022) - Wirth, Thomas; Namer, Izzie Jacques; Monga, Ben; Bund, Caroline; Iosif, Andra Valentina; Gebus, Odile; Montaut, Solveig; Bogdan, Thomas; Robelin, Laura; Renaud, Mathilde; Kremer, Stéphane; Tranchant, Christine; et al.
Abstract : Objectives: Nigrostriatal dopaminergic denervation (NSDD) remains poorly characterized in cerebellar multiple system atrophy (MSA-C). We aimed to study NSDD progression in MSA-C and evaluate the capacity for [123I]-FP-CIT-SPECT and parkinsonism to differentiate MSA-C from idiopathic late-onset cerebellar ataxia (ILOCA). Methods: We included 85 patients successively referred for sporadic late-onset cerebellar ataxia (SLOCA). Every 6 months, SARA, UPDRS-III, and SDFS scores were measured, and MSA-C diagnostic criteria were searched for. Striatal/occipital dopaminergic binding ratio was evaluated every year with [123I]-FP-CIT-scintigraphy. Results: After a mean follow-up of 33.8 months, 33 patients had probable MSA-C, 8 possible MSA-C, and 44 ILOCA. SARA and UPDRS-III scores worsened faster in the probable MSA-C group ( p < 0.01) compared with the ILOCA group. The baseline striatal/occipital ratio was lower (2.3 vs 2.97; p < 0.01) and more decreasing among patients with probable MSA-C ( p < 0.01). Weighting dysautonomia and parkinsonism and/or NSDD as additional and principal criterion, respectively, in the possible MSA-C diagnostic criteria slightly improved their specificity (81.6% vs 76.9%) and sensitivity (77.8% vs 72.2%) to predict a final diagnosis of probable MSA-C. Discussion: Rapid symptom worsening and NSDD existence and progression predict MSA-C among patients with SLOCA. Parkinsonism, NSDD, and dysautonomia should be considered equivalent for possible MSA-C diagnosis.